Association of Serum Bilirubin With Metabolic Syndrome and Non-Alcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis - Liang, Chen; Yu, Zhiyuan; Bai, Li; Hou, Wei; Tang, Shan; Zhang, Wei; Chen, Xinyue; Hu, Zhongjie; Duan, Zhongping; Zheng, Sujun (Frontiers in Endocrinology, 2022)
Objective: Metabolic syndrome (MetS) and non-alcoholic fatty liver disease (NAFLD) are the leadingchronic diseases worldwide. There are still many controversies about the association between serum bilirubin and MetS or NAFLD. Thus, this study aims to evaluate the association of serum total bilirubin (TBIL), direct bilirubin (DBIL), indirect bilirubin (IBIL) with MetS and NAFLD. Methods: Multiple databases were searched for relevant studies until November 2021. Randomized controlled trials, cross-sectional and cohort studies evaluating the association between serum bilirubin levels and MetS or NAFLD were included. Results: Twenty-four cross-sectional and cohort studies with 101, 517 participants were finally analyzed. Fifteen studies and 6 studies evaluated the association between bilirubin and MetS or NAFLD in health screening population, respectively, while 3 studies evaluated the association between bilirubin and non-alcoholic steatohepatitis(NASH) in NAFLD patients. Random effect model analysis showed the inverse association between TBIL and MetS in male (95%CI=0.71-0.96) and gender-neutral(95%CI=0.61-0.91) group. However, no significant association was found in females. Notably, the inverse association between DBIL and MetS was noticed in male (95%CI=0.36-0.75), female (95%CI=0.16-0.58) and gender-neutral population (95%CI=0.67-0.92). IBIL level was inversely associated with MetS in females(95%CI=0.52-0.96), whereas no statistical correlation presented in males. Analysis showed no statistical correlation between TBIL and NAFLD in gender-neutral or male subgroup. Similarly, there were no association between DBIL or IBIL and NAFLD in gender-neutral subgroup. However, the negative correlation between DBIL and NAFLD existed in males(95%CI=0.76-0.96). In NAFLD patients, IBIL analysis showed inverse association with NASH(95%CI=0.01-0.12). Conclusion: Levels of serum TBIL and DBIL, especially serum DBIL, supporting an inverse connection with MetS in healthy population. Serum IBIL is inverse association with the onset and degree of NASH in NAFLD patients. Regulation of bilirubin metabolic pathways may be a potential strategy and exogenous bilirubin supplement may be a medicine to assist in lowering the risk of developing MetS and NAFLD. Systematic Review Registration: [PROSPERO], identifier [CRD42021293349]